Does plant immunity play a critical role during initiation of the legume-rhizobium symbiosis? - Tóth, Katalin; Stacey, Gary (Frontiers in Plant Science, 2015)
Plants are exposed to many different microbes in their habitat. These microbes may be benign or pathogenic, but in some cases they are beneficial. The rhizosphere provides an especially rich palette for colonization by beneficial (associative and symbiotic) microorganisms, which raises the question as to how roots can distinguish such ‘friends’ from possible ‘foes’ (i.e., pathogens). Plants possess an innate immunity system that can recognize pathogens, through an arsenal of protein receptors. These receptors include receptor-like kinases (RLK) and receptor-like proteins (RLP) located at the plasma membrane, as well as intracellular receptors (so called NBS-LRR proteins or R proteins) that recognize molecules released by microbes into the plant cell. The key rhizobial, symbiotic signaling molecule (called Nod factor) is perceived by the host legume plant using LysM-domain containing RLKs. Perception of the symbiotic Nod factor triggers signaling cascades leading to bacterial infection and accommodation of the symbiont in a newly formed root organ, the nodule, resulting in a nitrogen-fixing root nodule symbiosis (RNS). The net result of this symbiosis is the intracellular colonization of the plant with thousands of bacteria; a process that seems to occur in spite of the immune ability of plants to prevent pathogen infection. In this review, we discuss the potential of the invading rhizobial symbiont to actively avoid this innate immunity response, as well as specific examples of where the plant immune response may modulate rhizobial infection and host range.